(untitled) (MAUSAM, 1983)
An algorithm for computation of the parameters of a quasi-stationary barotropic planetary boundary layer (PBL) IS discussed. On the basis f the results of a number of numerical experiments, relations between the observed meteorological fields and the Internal parameters of the PBL have been established. A method is proposed to parameterize eddy momentum flux and frictional vertical velocity for their use in multi-level primitive equations (PE) models.